Gut Microbiota: The Next-Gen Frontier in Preventive and Therapeutic Medicine? - Nagpal, Ravinder; Yadav, Hariom; Marotta, Francesco (Frontiers in Medicine, 2014)
Our gut harbors an extremely diverse collection of trillions of microbes that, besides degrading the complex dietary constituents, execute numerous activities vital for our metabolism and immune health. Although the importance of gut microbiota in maintaining digestive health has long been believed, its close correlation with numerous chronic ailments has recently been exposed, thanks to the innovative mechanistic studies on the compositional and functional aspects of gut microbial communities using germ-free or humanized animal models. Since a myriad of mysteries about the precise structures and functions of gut microbial communities in specific health situations still remains to be explicated, the emerging field of gut microbiota remains a foremost objective of research for microbiologists, computational biologists, clinicians, nutritionalists etc. Nevertheless, it is only after a comprehensive understanding of the structure, density and function of the gut microbiota that the new therapeutic targets could be captured and utilized for a healthier gut as well as overall wellbeing.